Two new species of Anthurium sect. Andiphilum (Araceae) from Mexico - Jiménez, Pedro Díaz; Pérez-Farrera, Miguel Ángel; Croat, Thomas B.; Cedeño-Fonseca, Marco; Gómez-Domínguez, Héctor; Ortiz, Orlando O.; Aguilar-Rodríguez, Pedro A. (Phytotaxa, 2020)
Anthurium is represented in Mexico by 57 taxa (47 species and 10 infraspecific taxa), seven of which are endemic to the state of Oaxaca. During fieldwork in 2019 in the Ejido La Luz, Ixtlán de Juárez, Oaxaca, we discovered two undescribed terrestrial species belonging to Anthurium sect. Andiphilum from Mexico. Anthurium ixtlanense and A. luzense, are taxonomically described and illustrated.